The Effect of Ziswaf Acceptance, Giro Wadiah Savings, and Murabahah Income on Bonus Wadiah With Firm Size as A Moderating Variable for The Period of 2018.Q1 to 2023.Q3 - Asrul Yatimi, Muh.; Hestya Budianto, Eka Wahyu (UIN Mataram, 2024)
This study aims to determine and examine the effect of ZISWAF Fund Revenue, Wadiah Current Account Deposits, and Murabahah Income on Wadiah Bonus with Firm Size. The sample used in this study is a company in the financial sector listed on the Indonesia Stock Exchange (IDX) in 2018-2023. The sampling technique used was purposive sampling, with a total sample of 5 companies for 5 years. The data analysis technique used is Panel Data Regression Analysis and Moderated Regression Analysis (MRA) with the Eviews 12 application. The results showed that the receipt of ziswaf funds had no significant effect on the financial sector wadiah bonus for the 2018-2023 period. Wadiah current account deposits have a significant positive effect on wadiah bonuses in the financial sector for the 2018-2023 period. Murabahah income has no significant effect on bonus wadiah financial sector for the period 2018-2023. firm size cannot moderate the effect of ziswaf fund receipts on bonus wadiah financial sector in the 2018-2023 period. firm size can moderate the effect of wadiah current account deposits on bonus wadiah financial sector in the 2018-2023 period. firm size cannot moderate the effect of murabahah income on bonus wadiah financial sector in the 2018-2023 period. In future studies, it is expected to use other variables as moderating variables, such as BOPO and use a sample of companies from other sectors so that the results of the study will be more accurate.